WORK AND FAMILY ENRICHMENT AMONG DUAL CAREER UNIVERSITY PROFESSORS IN PAKISTAN: A QUALITATIVE INSIGHT - Farooqi, Yasir Aftab; Rehman, Dr. Chaudhry Abdul; Rehman, Dr. Sumaira (The journal of contemporary issues in business and government, 2021)
Of late, organizational behavior literature details the notion of work-family enrichment and more attention was gained by the said concept. However, in previous studies supporting emerges from the work and family front has ignored. The purpose of this research is to qualitatively explore the role of family and work as predictors of family-to-work enrichment (FWE) and work-to-family enrichment (WFE) among dual-career employees in higher education institutions of Pakistan. Data were gathered through the semi-structured interview from 22 faculty members of universities. Further, thematic analysis was applied by using NVivo-11 software. Findings supported the family support and also the work support for developing both work-to-family and family-to-work enrichment. The research signals the significance of ensuring organizational support for having effective employees. This study extends the literature of work and family by including role support for having FEW and WEF which is rarely studied in the Pakistani context.